2015
DOI: 10.1099/jmm.0.000064
|View full text |Cite
|
Sign up to set email alerts
|

Screening urine samples for the absence of urinary tract infection using the sediMAX automated microscopy analyser

Abstract: Urinalysis culminates in a workload skew within the clinical microbiology laboratory. Routine processing involves screening via manual microscopy or biochemical dipstick measurement, followed by culture for each sample. Despite this, as many as 80 % of specimens are reported as negative; thus, there is vast wastage of resources and time, as well as delayed turnaround time of results as numerous negative cultures fulfil their required incubation time. Automation provides the potential for streamlining sample sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In our study, we found that the bacteriuria parameter of the Dongjui DJ-8602 urine sediment analyzer, which uses an image analysis method has poor discriminatory power for UTI. Our results are consistent with other studies that the bacteriuria parameter with automated microscopy cannot be used alone to reduce the number of negative urine culture samples [17][18][19][20].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that the bacteriuria parameter of the Dongjui DJ-8602 urine sediment analyzer, which uses an image analysis method has poor discriminatory power for UTI. Our results are consistent with other studies that the bacteriuria parameter with automated microscopy cannot be used alone to reduce the number of negative urine culture samples [17][18][19][20].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, greater than 50% of samples in the study by Inigo et al originated from inpatients and both studies included specimens from catheterised patients [3, 4]. In contrast to those findings, Sterry-Blunt et al [6] reported from a study of 1411 samples that the highest achievable negative predictive value when using white blood cell and bacterial count thresholds was 89·1% and concluded that the SediMAX should not be used as a screening method prior to culture.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no other observational studies of this magnitude for the study of urine analysis for the diagnosis of UTIs. Most previous studies with the objective of predicting urine culture based on variables generated from sediment analysis, flow cytometry, and/or dip-stick testing have been controlled studies of a few hundred patients, with little consistency in the inclusion criteria [3, 4, 6, 13, 2729]. Prior efforts to establish a heuristic model based on microscopy thresholds generated conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Urine culture is still the gold standard for the microbiological confirmation of UTIs; however, it takes 24 to 48 h to provide results. The use of screening methods, such as traditional Gram staining or other methods for counting urine particles, like flow cytometry or automated microscopic urine sediment analysis, allow the prompt prediction of negative samples and a preliminary identification of microorganisms in positive samples (4)(5)(6)(7). Nevertheless, this information obtained from these methods is insufficient and requires culture and other biochemical tests.…”
mentioning
confidence: 99%